Two polymorphic Co(ii) field-induced single-ion magnets with enormous angular distortion from the ideal octahedron - Nemec, I; Herchel, R; Trávníček, Z (Dalton transactions (Cambridge, England, 2018)
A mononuclear complex [Co(neo)(PhCOO)2,], neo = neocuproine, PhCOO- = the benzoate anion, was prepared in two polymorph forms crystallizing in the C2/c, (1) and P21/c, (2) space groups. The polymorphs differ in the Co-O bond lengths and the level of trigonal distortion of their coordination polyhedra. The static and dynamic magnetic properties of these compounds were thoroughly studied by experimental (magnetometry) and theoretical (ab initio calculations) methods. The analysis of magnetic data was performed using the spin Hamiltonian formalism or the L-S model considering also the orbital angular momentum. It was revealed that both polymorphs possess a very large magnetic anisotropy with a pronounced rhombic character leading to the separation of the Kramers doublets larger than 120 cm-1. The measurements of alternating current susceptibility revealed that both polymorphs behave as field induced single molecule magnets with a small barrier of spin reversal (U = 22.1 K (for 1) and 17.1 K (for 2)) which indicates that relaxation processes other than the thermally activated Orbach process take place.